Trends in overweight and obesity by socioeconomic status in Year 6 school children, Australian Capital Territory, 2006-2018 - Zongjian Yang; Hai Phung; Ann-Maree Hughes; Sommer Sherwood; Emily Harper; Paul Kelly (BMC, 2019)
Abstract Background Due to the high prevalence and adverse consequences, overweight and obesity in children continues to be a major public health concern worldwide. Socioeconomic background and health-related behaviours (such as diet, physical activity and sedentary behaviors) are important factors associated with weight status in children. Using a series of height and weight assessments from the Australian Capital Territory Physical Activity and Nutrition Survey (ACTPANS), trends in prevalence of overweight and obesity by socioeconomic status were examined in ACT Year 6 school children between 2006 and 2018. Methods The ACTPANS has been conducted every 3 years since 2006. A total of 6729 children were surveyed. Complete data on height and weight were available for 6384 (94.9%) participants. Trends in the prevalence of overweight and obesity and associations between weight status and risk factors (such as socioeconomic status, physical activity, screen time and consumption of sugar-sweetened soft drinks (SSD)) were examined using logistic regression. Results The prevalence of overweight and obesity remained stable in girls (from 22.5% in 2006 to 21.6% in 2018) but declined in boys (from 27.8 to 17.9%). During the same period, levels of physical activity increased slightly, while screen time and the consumption of fast food and SSD decreased. Socioeconomic gradient, based on the school-level Index of Community Socio-Educational Advantage (ICSEA), was highly associated with prevalence of overweight and obesity. Since 2006, the estimated prevalence of overweight and obesity has remained high in the lowest SES groups, but a concurrent downward trend was observed in the highest SES group, leading to increasing disparity between SES groups. Children in the lowest ICSEA quintile were more likely to be overweight or obese compared to those in the moderate and highest ICSEA quintiles. Children in lower ICSEA quintiles also reported lower levels of physical activity, higher levels of screen time, and higher levels of fast food and SSD consumption compared to those in higher ICSEA quintiles. Conclusions While recent trends in overweight and obesity in ACT children are encouraging, the prevalence remains unacceptably high, especially in those from low socioeconomic backgrounds. Additional prevention efforts are required to address the socioeconomic disparity.